Role of oxidative stress in cadmium toxicity and carcinogenesis - Liu, Jie; Qu, Wei; Kadiiska, Maria B. (Toxicology and applied pharmacology, 2009)
Cadmium (Cd) is a toxic metal, targeting the lung, liver, kidney, and testes following acute intoxication, and causing nephrotoxicity, immunotoxicity, osteotoxicity and tumors after prolonged exposures. Reactive oxygen species (ROS) are often implicated in Cd toxicology. This minireview focused on direct evidence for the generation of free radicals in intact animals following acute Cd overload and discussed the association of ROS in chronic Cd toxicity and carcinogenesis. Cd-generated superoxide anion, hydrogen peroxide, and hydroxyl radicals in vivo have been detected by the electron spin resonance spectra, which are often accompanied by activation of redox sensitive transcription factors (e.g., NF-κB, AP-1 and Nrf2) and alteration of ROS-related gene expression. It is generally agreed upon that oxidative stress plays important roles in acute Cd poisoning. However, following long-term Cd exposure at environmentally-relevant low levels, direct evidence for oxidative stress is often obscure. Alterations in ROS-related gene expression during chronic exposures are also less significant compared to acute Cd poisoning. This is probably due to induced adaptation mechanisms (e.g., metallothionein and glutathione) following chronic Cd exposures, which in turn diminish Cd-induced oxidative stress. In chronic Cd-transformed cells, less ROS signals are detected with fluorescence probes. Acquired apoptotic tolerance renders damaged cells to proliferate with inherent oxidative DNA lesions, potentially leading to tumorigenesis. Thus, ROS are generated following acute Cd overload and play important roles in tissue damage. Adaptation to chronic Cd exposure reduces ROS production, but acquired Cd tolerance with aberrant gene expression plays important roles in chronic Cd toxicity and carcinogenesis.